Evaluation of Humoral and Cellular Responses in SARS-CoV-2 mRNA Vaccinated Immunocompromised Patients - Oyaert, Matthijs; De Scheerder, Marie-Angélique; Van Herrewege, Sophie; Laureys, Guy; Van Assche, Sofie; Cambron, Melissa; Naesens, Leslie; Hoste, Levi; Claes, Karlien; Haerynck, Filomeen; Kerre, Tessa; Van Laecke, Steven; et al. (Frontiers in Immunology, 2022)
Background Immunocompromised patients are at increased risk of severe COVID-19 and impaired vaccine response. In this observational prospective study, we evaluated immunogenicity of the BNT162b2 mRNA vaccine in cohorts of primary or secondary immunocompromised patients in follow-up at the Ghent University Hospital. Methods Five clinical groups of immunocompromised patients [primary immunodeficiency (PID) (n=57), people living with HIV (PLWH) (n=27), secondary immunocompromised patients with a broad variety of underlying rheumatologic (n=23) and homogeneous (multiple sclerosis) neurologic (n=53) conditions and chronic kidney disease (CKD) (n=39)] as well as a healthy control group (n=54) were included. Systemic humoral and cellular immune responses were evaluated by determination of anti-SARS-CoV-2 Spike antibodies using a TrimericS IgG assay (Diasorin) and through quantification of interferon gamma in response to SARS-CoV-2 antigen with QuantiFERON SARS-CoV-2 assay (Qiagen), respectively. Responses were measured at pre-defined time-points after complete vaccination. Results All healthy controls, PLWH and CKD-patients had detectable antibodies 10 to 14 days (T2) and 3 months (T3) after administration of the second vaccination. In contrast, 94.5% of the PID, 50.0% of the rheumatologic and 48.0% of neurologic patients developed antibodies at T2 and 89.1% of the PID, 52.4% of the rheumatologic and 50.0% of neurologic patients developed antibodies at T3. No significant differences in cellular response between the healthy control group and the PLWH and CKD groups were determined at T3, while proportions of reactive subjects were lower in PID and rheumatologic patients and higher in neurologic patients. Humoral and cellular immune responses significantly correlated in the healthy control, PID, PLWH groups for all 3 antigens. Conclusion Patients with acquired or inherited immune disorders may show variable immune responses to vaccination with the BNT162b2 mRNA vaccine against SARS-CoV-2. Whether humoral, cellular or both immunogenicity is delayed depends on the patient group, therapy and individual risk factors. These data may guide the counselling of patients with immune disorders regarding vaccination of SARS-CoV-2.